2007
DOI: 10.1080/10401230701653294
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in Depression

Abstract: Women have higher rates of depression and can often present differently than do men. Further research can ascertain which combination of factors increase women's risk. The effect of pregnancy and the impact of the menstrual cycle on the course of all depressive disorders need increased attention. Large prospective randomized controlled trials with gender differences in treatment response as the primary endpoint are necessary in order to answer the now controversial question of gender differences in antidepress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
1
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(158 citation statements)
references
References 91 publications
11
127
1
16
Order By: Relevance
“…Sex differences in response to endotoxin M Moieni et al (Grigoriadis and Robinson, 2007;Weissman et al, 1996). For example, in the present study, females (vs males) showed greater increases in depressed mood in response to endotoxin, indicating that females may be more sensitive to the affective consequences of inflammation, which given the potential role of inflammation in the pathogenesis of depression (Raison and Miller, 2011), may contribute to the increased likelihood for females to develop depressive disorders.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Sex differences in response to endotoxin M Moieni et al (Grigoriadis and Robinson, 2007;Weissman et al, 1996). For example, in the present study, females (vs males) showed greater increases in depressed mood in response to endotoxin, indicating that females may be more sensitive to the affective consequences of inflammation, which given the potential role of inflammation in the pathogenesis of depression (Raison and Miller, 2011), may contribute to the increased likelihood for females to develop depressive disorders.…”
Section: Discussionmentioning
confidence: 45%
“…In fact, the vast majority of studies investigating the effects of inflammation in relation to depressive symptoms have been conducted in males (reviewed in Schedlowski et al, 2014). Given that females are at a greater risk for depression (Grigoriadis and Robinson, 2007), are more sensitive to social cues (Cyranowski et al, 2000), and show greater inflammatory reactivity (O'Connor et al, 2007), it is important to examine whether females are more susceptible to inflammation-induced socioemotional changes, which may increase risk for depression.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that gender disparities in depression increase after early to mid-adolescence, and are especially large at reproductive ages (Nolen-Hoeksema and Girgus 1994;Hankin et al 1998;Grigoriadis and Erlick Robinson 2007). Generally, it appears that women are more likely than men to suffer from depression though old age as well (Cairney and Wade 2002;Djernes 2006).…”
Section: Sex Differences In Depressionmentioning
confidence: 99%
“…A variety of bio-physiological, psychosocial and behaviour-related explanations have been described for these sex differences (Grigoriadis and Robinson, 2007;Parker and Brotchie, 2010). Concerning self-reported diagnosed depression, sexspecific help-seeking behaviour due to different extents of stigmatization and sex-specific reporting of symptoms should be considered as additional explanations (Hammer et al, 2013;Latalova et al, 2014;Möller-Leimkühler, 2002).…”
Section: Socio-demographic Correlatesmentioning
confidence: 99%